Letter from James Curtis Booth to Mr. Samuel B. Brown - Booth, James Curtis (1884)
James Curtis Booth (1810-1888) writes to Samuel B. Brown to discuss rent that is due on his farm.
Keywords: Booth, James Curtis, 1810-1888